P‐166: Bistable Operation of a Smectic‐A Liquid Crystal Grating for Low‐power Window Display Application. Issue 1 (29th May 2019) - Seo, Jeong-Ho; Huh, Jae-Won; Choi, Tae-Hoon; Kim, Jin-Hun; Woo, Jae-Hyeon; Yoon, Tae-Hoon
Abstract : We report a bistable smectic‐A (SmA) liquid crystal (LC) cell with crossed interdigitated electrodes. An SmA‐LC cell with crossed interdigitated electrodes is switchable between haze‐free transparent and high‐haze translucent states. It can be operated with very little power because it consumes power only while the state is being switched. Owing to the high diffraction efficiency, it can provide a high haze value of 92.2% in the translucent state. It has shown a clear transparent state with little haze and excellent optical characteristics in the translucent state. We expect that the device will be used for a window display application.